Balancing Public Interest with Property Rights in Indonesian and Kenya Toll Road Acquisition: Menyeimbangkan Kepentingan Umum dengan Hak Milik dalam Pembebasan Lahan untuk Jalan Tol di Indonesia dan Kenya - Rendy Dwiandika; Moh. Fadli; Reka Dewantara; Istislam Istislam (Rechtsidee, 2026)
General Background: Toll road development requires states to reconcile infrastructure objectives with constitutional protection of private property. Specific Background: In Indonesia and Kenya, land acquisition for commercially operated toll roads under Public Private Partnership schemes raises recurring questions concerning public interest, eminent domain, compensation, participation, and judicial protection. Knowledge Gap: Previous research largely addressed consultation, social conflict, or property protection within a single jurisdiction and did not comparatively examine commercial toll road acquisition across civil law and common law systems. Aims: This normative legal study compares statutory rules, constitutional provisions, legal doctrines, and jurisprudence governing toll road land acquisition in Indonesia and Kenya through comparative and conceptual approaches. Results: Both jurisdictions face difficulties in defining public interest and securing fair compensation for commercially operated infrastructure; Indonesia emphasizes procedural certainty, whereas Kenya allows broader substantive judicial review. Novelty: The study connects divergent legal traditions within one comparative framework focused specifically on eminent domain for commercial toll road partnerships. Implications: A balanced legal model requires proportionality, meaningful public participation, comprehensive compensation, livelihood-sensitive protection for vulnerable groups, and effective judicial safeguards. Highlights: One jurisdiction prioritizes procedural certainty, while the other permits broader substantive judicial review. Commercial infrastructure schemes complicate definitions of public interest and fair compensation. Proportionality, meaningful participation, comprehensive payment, and court protection form the proposed model. Keywords: Public Interest, Property Rights, Toll Road Land Acquisition